Heavy Metal Exposure in Alport Syndrome in an Adolescent: A Case Report: Heavy Metal Exposure in Alport Syndrome - Leventoğlu, Emre; Uzun Kenan, Bahriye; Öğüt, Betül; Büyükkaragöz, Bahar; Işık Gönül, İpek and Fidan, Kibriya (Journal of Pediatric Nephrology, 2024)
Alport syndrome is an inherited glomerular disease characterized by hematuria, proteinuria, hypertension, progressive kidney failure, hearing loss, and ocular pathologies. It is caused by a mutation in COL4A3, COL4A4, or COL4A5 genes. A lamellar or uniformly thinned glomerular basement membrane is a pathognomonic histologic appearance for Alport syndrome. Light microscopy shows nonspecific findings, including mesangial matrix expansion and hypercellularity. Renal tubules are other main components of the kidney and the major sites in response to injuries. They are vulnerable to various conditions, such as hypoxia, proteinuria, and nephrotoxic substances, including heavy metals, like lead and mercury. We demonstrated that a patient with asymptomatic Alport syndrome may have accelerated worsening of kidney functions due to occupational exposure to lead and mercury. Regarding the initial diagnosis with current clinical and laboratory findings in patients, it is noteworthy that there is always the possibility of another pathology, and additional investigations may be needed. Besides, when considering public health issues and the financial burden due to occupational diseases, we desired to draw attention to the importance and need to create safer work environments and make frequent inspections.